2016
DOI: 10.1590/0037-8682-0147-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sandflies (Diptera: Psychodidae) in an urban area of Northeastern Brazil

Abstract: Introduction:The sandfl y fauna is well studied globally. In Brazil, sandfl y fauna is very diverse in the Northeast region, especially in states such as Maranhão, Ceará, and Bahia. However, in the State of Pernambuco, the distribution of these insects is still not well known. Therefore, the objective of this study was to identify the different species that constitute the sandfl y fauna in an urban area in the Northeast region of Brazil, where an outbreak of visceral leishmaniasis (VL) was recently reported. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Similar studies conducted in Pernambuco reported a species richness ranging between 4–25 species [6, 27, 3032]. Until this study, 41 sand fly species were considered to be present in Pernambuco [29].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar studies conducted in Pernambuco reported a species richness ranging between 4–25 species [6, 27, 3032]. Until this study, 41 sand fly species were considered to be present in Pernambuco [29].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, some of the houses were surrounded by native vegetation, which may have favoured the encounter of M. capixaba in their interior. A study carried out in São Vicente Férrer (agreste region of Pernambuco) [30] reported a single female in the peridomicile and 24 males and 31 females in the forest environment. In Caruaru (agreste region of Pernambuco) [31] reported only three females of M. capixaba in the intradomicile.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of LV and LC entails an ecological and epidemiology association that is directly tied to the spread and distribution of phlebotomine species. Some wild species of phlebotoms have spread around human dwellings and animal shelters in rural and urban peridomicilian regions of Brazil because of environmental and climate changes caused by deforestation and urbanization processes, demonstrating their adaptation to humans-modi ed environments (Agra et al 2016). As a result, investigating and comprehending this relationship provides pertinent information in the eld of epidemiology, allowing for the acquisition of knowledge about the transmission dynamics, the host's guard function, and the risks of disease manifestation (Aysanoa et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some entomological surveys have been conducted in northeastern Brazil (GUIMARÃES et al, 2012;COSTA et al, 2013;MIRANDA et al, 2015;AGRA et al, 2016), but mostly in the interior of this region, while the coast has been less explored (LUCENA et al, 1984;SILVA et al, 2017a). In northeastern Brazil, Lutzomyia whitmani has generally been one of the more common species incriminated as a vector for L. braziliensis, whereas L. longipalpis is considered to be the most important transmitter of L. infantum (ANDRADE-FILHO et al, 2017;SILVA et al, 2017b;PESSOA-E-SILVA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%